Evaluation of Internet-Based Training in Trauma Care for Nurses in Mental Health Welfare Centers: A Cluster Randomized Controlled Trial - Sunah Kim; Go-Un Kim; Jinyoung Park (SAGE Publishing, 2023)
Objective: This study evaluates the efficacy of Internet-Based Training in Trauma Care for Nurses (IBTTCN) to improve nurses' trauma intervention self-efficacy, professional quality of life, and attitudes and knowledge about post-traumatic stress disorder. Methods: Forty-one nurses participated from May to July 2021. The assessment points were at baseline (T1), immediately after program completion (4 weeks; T2), and 1 month after T2 (T3). Data were analyzed using repeated-measures analysis and generalized estimating equations. Results: In the intervention group, trauma intervention self-efficacy increased significantly after the IBTTCN, and the effect of such self-efficacy over time was significant. Conclusions: The IBTTCN improved nurses' trauma intervention self-efficacy.